Analysis of Students’ Critical Thinking Skills on Virtual Reality Learning Media - Faradila Aulia Alifteria; Tjipto Prastowo; Nadi Suprapto (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2023)
This study aims to describe students’ critical thinking skills and the corresponding prior knowledge of Virtual Reality (VR) media used for learning purposes in a classroom setting. A total of 65 high school students from Grade XI Science 1 and Science 2 were involved as respondents in this preliminary research using qualitative-descriptive analysis. The instrument used included questionnaires (distributed over the respondents) containing 12 questions on VR relevant to the indicators of critical thinking skills. The results showed students' skills in critical thinking at the intermediate level. The indicator of analytical ability has the highest percentage in the medium category. The number of students with critical thinking skills in the high category is 14, and in the medium category, as many as 51 students. Students' prior knowledge of VR media (familiar with the technology) was reported to 46.00% of all the respondents, and the remaining 54.00% did not know what it was. However, all the respondents were interested and happy with VR media as a learning tool. Improvement of critical thinking skills could be achieved through contextual learning and VR learning media. The implication of the present study for future use of VR education media in schools is possible as VR media is considered to be technology-assisted learning, applicable to science and physics teachers when delivering learning materials in class.